IMPLEMENTASI PERMA TENTANG PENYESUAIAN BATASAN TINDAK PIDANA RINGAN DAN JUMLAH DENDA DALAM KUHP UNTUK MEWUJUDKAN PERLINDUNGAN HUKUM - Ni Nengah Agustin Citrawati; Sulistyawati, Ni Putu Yunika; Dapa Ate, Fridoerichas (Kerta Dyatmika, 2026)
One of the problems that is often faced by a criminal justice system in Indonesia is the high number of cases that enter the court. This not only burdens the judiciary, but also slows the settlement of the case. One type of case that often piles up in court is a minor crime, which should be handled with simpler procedures. Responding to the issue, the Supreme Court issued Perma No. 2 of 2012 which aims to provide guidelines for judges in handling minor criminal acts more effectively even though the purpose of this Perma is very good but, in fact in the field there are still irregularities in its application. The purpose of this study carried out the Tri Dharma of Higher Education, especially in the field of research conducted by students and this study aims to analyze the types of minor criminal acts regulated in the Criminal Code and the Implementation of Perma No. 2 of 2012 concerning adjusting the limits of minor criminal acts and the number of fines in the Criminal Code on handling minor criminal acts to realize legal protection and provide recommendations to improve the benefits of applying the regulation and provide input for the improvement of the criminal justice system in Indonesia. used in this study is an empirical type of research with this research is descriptive. The results of this study are minor criminal acts to realize legal protection impact on increasing the evisiency of handling minor criminal acts, especially in the conflict of the judicial process. CONCLUSION This study was the implementation of this Perma by emphasizing the amount of loss suffered by victims which were originally only two hundred and fifty rupiah, contained in Article 379, 407, 364, 384, 382 and Article 373 of the Criminal Code, replaced as Rp. 2,500,000(two million five hundred thousand